Characterization and emulation of a new supercapacitor-type energy storage device - Kulsangcharoen, Ponggorn (2013)
The work in this thesis focuses on the characterization, modeling and emulation of both the supercapacitor and the new supercapattery energy storage device. The characterization involves the selection of dynamic models and experimental methodologies to derive model parameters. The characterizing processes focus on predicting short-term device dynamics, energy retention (self-discharging) and losses and round-trip efficiency. A methodology involving a pulse current method is applied for the first time to identify a model parameter to give fast device dynamic characteristics and a new constant power cycling method is used for evaluating round-trip efficiency. Experimental results are shown for a number of supercapacitor and supercapattery devices and good results are obtained. The derived models from the characterization results are implemented into the emulator system and the emulator system is used to mimic the dynamic characteristics of a scaled-up 1kW supercapattery device. The thesis also addresses voltage equalizing circuits and reports a study that investigates efficiency, a cell voltage deviation and voltage equalizing time for different control methods.